Changes in Therapy Utilization at Skilled Nursing Facilities Under Medicare's Patient Driven Payment Model - Zhang, Wei; Luck, Jeff; Patil, Vaishali; Mendez-Luck, Carolyn A; Kaiser, Alexandra (Journal of the American Medical Directors Association, 2022)
The Patient Driven Payment Model (PDPM) was implemented in October 2019 to reimburse skilled nursing facilities (SNFs) based on Medicare patients' clinical and functional characteristics rather than the volume of services provided. This study aimed to examine the changes in therapy utilization and quality of care under PDPM.OBJECTIVESThe Patient Driven Payment Model (PDPM) was implemented in October 2019 to reimburse skilled nursing facilities (SNFs) based on Medicare patients' clinical and functional characteristics rather than the volume of services provided. This study aimed to examine the changes in therapy utilization and quality of care under PDPM.Quasi-experimental design.DESIGNQuasi-experimental design.In total, 35,540 short stays by 27,967 unique patients in 121 Oregon SNFs.SETTING AND PARTICIPANTSIn total, 35,540 short stays by 27,967 unique patients in 121 Oregon SNFs.Using Minimum Data Set data from January 2019 to February 2020, we compared therapy utilization and quality of care for Medicare short stays before and after PDPM implementation to non-Medicare short stays.METHODSUsing Minimum Data Set data from January 2019 to February 2020, we compared therapy utilization and quality of care for Medicare short stays before and after PDPM implementation to non-Medicare short stays.The number of minutes of individual occupational therapy (OT) and physical therapy (PT) per week for Medicare stays decreased by 19.3% (P < .001) and 19.0% (P < .001), respectively, in the first 5 months of PDPM implementation (before the COVID-19 pandemic). The number of group OT and PT minutes increased by 1.67 (P < .001) and 1.77 (P < .001) minutes, respectively. The magnitude of PDPM effects varied widely across stays with different diagnoses. PDPM implementation was not associated with statistically significant changes in length of SNF stay (P = .549), discharge to the community (P = .208), or readmission to the SNF within 30 days (P = .684).RESULTSThe number of minutes of individual occupational therapy (OT) and physical therapy (PT) per week for Medicare stays decreased by 19.3% (P < .001) and 19.0% (P < .001), respectively, in the first 5 months of PDPM implementation (before the COVID-19 pandemic). The number of group OT and PT minutes increased by 1.67 (P < .001) and 1.77 (P < .001) minutes, respectively. The magnitude of PDPM effects varied widely across stays with different diagnoses. PDPM implementation was not associated with statistically significant changes in length of SNF stay (P = .549), discharge to the community (P = .208), or readmission to the SNF within 30 days (P = .684).SNFs responded to PDPM with a significant reduction in individual OT and PT utilization and a smaller increase in group OT and PT utilization. No changes were observed in length of SNF stay, rates of discharge to the community, or readmission to the SNF in the first 5 months of PDPM implementation. Further research should examine the relative effects of individual and group therapy and their impact on the quality of SNF care.CONCLUSIONS AND IMPLICATIONSSNFs responded to PDPM with a significant reduction in individual OT and PT utilization and a smaller increase in group OT and PT utilization. No changes were observed in length of SNF stay, rates of discharge to the community, or readmission to the SNF in the first 5 months of PDPM implementation. Further research should examine the relative effects of individual and group therapy and their impact on the quality of SNF care.